2017
DOI: 10.1001/jamainternmed.2017.1634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Attitudes Regarding Overuse of Inpatient Laboratory Testing With Health Care Provider Type

Abstract: Role of the Funder/Sponsor: The National Institutes of Diabetes and Digestive and Kidney Diseases had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication. Disclaimer:The interpretation and reporting of these data are the responsibility of the authors and in no way should be seen as an official policy or interpretation of the US government or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…However, nursing workflow can be complex. One study revealed that nurses view routine laboratory tests as more beneficial, 56 potentially because they can be scheduled when nursing workload is light. In our environment, nursing workflow and the lack of a dedicated phlebotomy team made afternoon laboratory tests difficult to obtain in a timely, reliable manner, so efforts to reduce early-morning laboratory tests ultimately were…”
Section: Figurementioning
confidence: 99%
“…However, nursing workflow can be complex. One study revealed that nurses view routine laboratory tests as more beneficial, 56 potentially because they can be scheduled when nursing workload is light. In our environment, nursing workflow and the lack of a dedicated phlebotomy team made afternoon laboratory tests difficult to obtain in a timely, reliable manner, so efforts to reduce early-morning laboratory tests ultimately were…”
Section: Figurementioning
confidence: 99%
“…The study was conducted at Memorial Sloan Kettering Cancer Center, a tertiary academic cancer hospital in New York City. The 12-item survey was adopted from a previously administered but not formally validated survey (Online-only Appendix) 5, 8 . The survey was pilot tested with 4 physicians, 3 NPs, 2 PAs, and 3 RNs and edited for content and clarity.…”
Section: Methodsmentioning
confidence: 99%
“…The 12-item survey was adopted from a previously administered but not formally validated survey (Online-only Appendix). 5,8 The survey was pilot tested with four physicians, three NPs, two PAs, and three RNs and edited for content and clarity. All staff providers including NPs, PAs, RNs, and resident, fellow, and attending MDs working in the hospital during the two-week survey period (November 2-15, 2015) were eligible to participate and were emailed a link to the survey.…”
Section: Survey Development and Administrationmentioning
confidence: 99%
“…To inform intervention development, we surveyed providers about lab-ordering preferences with use of questions from a prior survey to provide a benchmark (Appendix Table 2). 15 While reducing lab frequency was supported, the modal response for how frequently a stable patient should receive routine labs was every 48 hours (Appendix Table 2). Therefore, we hypothesized that labs ordered every 48 hours may be popular.…”
Section: Development Of Order Smarttmentioning
confidence: 99%